Procrastinators and hyperbolic discounters: Probability of transition from temporary to full-time employment - SunYoun Leea; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2012)
Temporary agency work (TAW) is believed to facilitate the matching between firms and on-the-job searchers. This leads to shortening of the unemployment and job search duration. On the other hand, firms that hire temporary workers have less incentive to train them, which makes it difficult for low-skilled temporary workers to find a better job in future. Current literature has not established whether TAW employment improves the welfare of either or both the employers and employees. Therefore, this paper examines the effect of TAW employment in the Japanese labor market on employment transitions focusing on individual time preferences. Investments in one's career involve a trade-off between immediate costs and later rewards, and thus, individual heterogeneity in time preferences may explain the behavioral patterns of labor force. We find that TAW employees have a tendency toward impatience and hyperbolic discounting. In addition, those who have held temporary job are less likely to move into full-time job positions, but no significant wage differences are observed. The strength of the negative effects on the transition probabilities declines over time but the significant effects remain over the following years. Our results indicate that TAW for employees in Japan is more likely to function as a dead-end rather than stepping stone toward stable full-time employment.
Keywords: D03; D90; J01; 330; time preferences; temporary employment; ATT estimation; Leiharbeit; Arbeitsmarktintegration; Dauer; Lohnstruktur; Japan